State Actors in Agrarian Conflicts - Rahmawati, Etika; Rahayu, Esmi Warassih Pudji; Sukirno, Sukirno (Journal of Southeast Asian Human Rights, 2023)
This study focuses on the involvement of state actors in agrarian conflict. Various policies have been introduced in order to resolve the agrarian conflicts. However, the existence of these policies did not necessarily bring about positive changes in the subsequent years. From 2012 to 2022 (a decade), agrarian conflicts have become increasingly uncontrollable. Throughout the year 2022, there were at least 212 eruptions of agrarian conflicts in various investment and corporate-based business sectors. Permits, concessions, and land rights continued to be granted to companies, even though these companies had caused numerous agrarian conflicts within the community. The implementation of the rule of law concept has not been able to be fully realized as it should. The ongoing agrarian conflicts have demonstrated how the state acts based on power when directly dealing with the community. Using the theories of legitimacy and space production, the issues regarding agrarian conflicts and the state actors involved will be analyzed in-depth. Keywords: Agrarian Conflict, State Actors, Rule of Law